Product Quality, Personal Selling, and Consumer Purchase Intention: An Empirical Investigation in the Retail Sector - Daniel Aritonang (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of product quality and personal selling on consumer purchasing interest in products at PT. Metro Sibolga. Based on the results of the research and data analysis that have been conducted, the results obtained are that product quality has a positive and significant effect on consumer purchasing interest. This shows that the better the quality of the product offered, the higher the consumer purchasing interest. In addition, personal selling has also been proven to have a positive and significant effect on consumer purchasing interest, which means that effective personal selling activities can increase consumer interest in making purchases. Simultaneously, product quality and personal selling have a positive and significant effect on consumer purchasing interest. Thus, the combination of good product quality and effective personal selling strategies can increase consumer purchasing interest in products at PT. Metro Sibolga.